Components of Comprehensive and Effective Transitional Care. Issue 6 (3rd April 2017) - Naylor, Mary D.; Shaid, Elizabeth C.; Carpenter, Deborah; Gass, Brianna; Levine, Carol; Li, Jing; Malley, Ann; McCauley, Kathleen; Nguyen, Huong Q.; Watson, Heather; Brock, Jane; Mittman, Brian; et al.
Abstract : Transitional care (TC) has received widespread attention from researchers, health system leaders, clinicians, and policy makers as they attempt to improve health outcomes and reduce preventable hospital readmissions, yet little is known about the critical elements of effective TC and how they relate to patients' and caregivers' needs and experiences. To address this gap, the Patient‐Centered Outcomes Research Institute (PCORI) funded a national study, A chieving patient‐centeredC are and optimizedH ealthI n care transitions byE valuating theV alue ofE vidence (Project ACHIEVE). A primary aim of the study is the identification of TC components that yield desired patient and caregiver outcomes. Project ACHIEVE established a multistakeholder workgroup to recommend essential TC components for vulnerable Medicare beneficiaries. Guided by a review of published evidence, the workgroup identified and defined a preliminary set of components and then analyzed how well the set aligned with real‐world patients' and caregivers' experiences. Through this process, the workgroup identified eight TC components: patient engagement, caregiver engagement, complexity and medication management, patient education, caregiver education, patients' and caregivers' well‐being, care continuity, and accountability. Although the degree of attention given to each component will vary based on the specific needs of patients and caregivers, workgroup members agree that health systems need to address all components to ensure optimal TC for all Medicare beneficiaries.